El Ordenamiento Educativo Kankuamo, como Escenario del Fortalecimiento de la Educación Propia, en el marco de los Derechos Indígenas en contextos de la Ciudadanía Multicultural (2022)
The present work of degree approaches the organization of a didactic material, integrating main guiding categories such as Own Education, Multicultural Citizenship and Indigenous Law, with the objective of strengthening the Kankuamo educational order, taking as reference three own pedagogical components comprised in: Identity, Territory and Self- determination. The work contemplated and made sense in terms of the articulation of the pedagogical guidelines, because it is a material that was built with the educational community, taking the spaces of observation and intervention in the field